Regression of hypertensive myocardial fibrosis by Na+/H+ exchange inhibition - Cingolani, Horacio Eugenio (2003)
We have recently reported that the inhibition of the Na+/H+ exchanger (NHE) during 1 month in spontaneously hypertensive rats (SHR) is followed by regression of cardiomyocyte hypertrophy but not of myocardial fibrosis. The aim of this study was to evaluate whether a treatment of longer duration could reduce myocardial fibrosis and stiffness. SHR received 3.0 mg/kg per day of the specific NHE-1 inhibitor cariporide; the effect on cardiomyocyte cross-sectional area, myocardial collagen volume fraction, collagen synthesis, and myocardial stiffness (length-tension relation in left papillary muscles) was evaluated at several time points (after 1, 2, or 3 months). A slight decrease of ≈5 mm Hg in systolic blood pressure was observed after 1 month of treatment with no further changes. After 2 and 3 months of treatment, the size of cardiomyocytes remained within normal values and myocardial fibrosis progressively decreased to normal level. Accordingly, myocardial stiffness and the serum levels of the carboxyterminal propeptide of procollagen type I, a marker of collagen type I synthesis, were normalized after 3 months. Left ventricular weight decreased from 910±43 (in untreated SHR) to 781±21 mg (treated SHR) after 3 months of treatment. No difference in body weight between treated and untreated SHR was observed after this period of treatment. The present data allow us to conclude that in the SHR the administration of an NHE-1 inhibitor for 2 or 3 months leads to the normalization of collagen type I synthesis, myocardial collagen volume fraction, and stiffness.